1996
DOI: 10.1096/fasebj.10.14.9002553
|View full text |Cite
|
Sign up to set email alerts
|

Inducible NO synthase II and neuronal NO synthase I are constitutively expressed in different structures of guinea pig skeletal muscle: implications for contractile function

Abstract: The expression of NOS isoforms was studied in guinea pig skeletal muscle at the mRNA and protein level, and the effect of NO on contractile response was examined. Ribonuclease protection analyses demonstrated NOS I and NOS II mRNAs in diaphragm and gastrocnemius muscle. In Western blots, NOS I and NOS II immunoreactivities were found in the particulate but not the soluble fraction of skeletal muscle. NOS activity was found almost exclusively in the particulate fraction. About 50% of this activity was Ca2+ inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
117
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 5 publications
9
117
0
1
Order By: Relevance
“…35 In skeletal muscle, iNOS was found mostly in a particulate fraction. 33 None of these studies, however, associated the increase of particulate iNOS with any effect on other cellular proteins.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…35 In skeletal muscle, iNOS was found mostly in a particulate fraction. 33 None of these studies, however, associated the increase of particulate iNOS with any effect on other cellular proteins.…”
Section: Discussionmentioning
confidence: 94%
“…32 Furthermore, nNOS was found predominantly in a particulate fraction in skeletal muscle. 33 Likewise, iNOS also exists in a particulate pool. Previous studies have shown a membranous subcellular location for as much as 50% of total cellular iNOS, 5 and a recent study showed that an iNOS-like enzyme is present in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…A 5-HT 2B -dependent transcriptional regulation of iNOS activity can be excluded because the steady state level of iNOS transcripts is found constant during the cell response. Therefore the possibility that, upon DOI-mediated induction, iNOS is turned on from an inactive state by post-translational controls only, has to be considered (44,45).…”
Section: Figmentioning
confidence: 99%
“…27 There are 3 types of NOS: neuronal (nNOS/NOS1), endothelial (eNOS/NOS3), and inducible (iNOS/NOS2). 2 Neuronal NOS is mainly expressed in neurons of the central 31 and peripheral nervous systems, but can also be found in other cells such as skeletal muscle myocytes, 10 lung epithelial cells, 3 and skin mast cells. 36 Endothelial NOS is mainly expressed by endothelial cells and can be found in neurons, 7 dermal fibroblasts, 40 epidermal keratinocytes, 36 thyroid follicular cells, 5 hepatocytes, and smooth muscle cells.…”
mentioning
confidence: 99%